Penggunaan Media Pembelajaran Card Match Circle Berbasis Budaya Melayu dalam Upaya Peningkatan Mutu Proses Pembelajaran di Sekolah Dasar - Marhadi, Hendri; Erlisnawati; Syafriyafdi, Non; Cindy, Vista; Uyun, Khurotul; Syahfrika, Elvina; Septiana, Lora; Harmadani, Putri; Andini, Suci (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Learning media is very important in improving the quality of the learning process in primary schools. In the learning process there are still many teachers who use conventional learning due to the lack of understanding and skills of teachers in using innovative learning media. This service aims to improve teachers' understanding of the benefits of learning media and the use of Card Match Circle (CMC) media for efforts to improve the quality of the learning process in elementary schools. Method: The service method used consists of four stages, namely sosialisation, training, technology application and evaluation and assistance. Results: The results of the service implementation show that there is an increase in teacher understanding of the use of CMC media with an N-Gain of 0.65 with a medium category and teacher understanding of the use of CMC media in learning with an N-Gain of 0.75 with a high category. CMC media can increase learning motivation and make it easier for students to receive learning materials. Conclusion: This service can be concluded that there is an increase in teacher understanding of CMC media and its use and CMC learning media is stated to improve the quality of the learning process in elementary schools.